Effect of split injection and injection pressure on CRDI engine fuelled with POME-diesel blend. (15th May 2021) - Pavan, P.; Bhaskar, K.; Sekar, S.
Highlights: Specific energy consumption with B20 blend was lower with pilot fuel up to 32° BTDC. Peak pressure inside the combustion was reduced with split injection technique. Pilot fuel technique reduced the HRR compared to single injection mode. Higher FIP with split injection showed lower tail pipe emissions except NO. Abstract: Due to the fast depleting fossil fuels and the stringent emission norms put forth by the environmental agencies like EPA made people in the industries and scientific communities to look for suitable alternatives for sustaining market growth. Biodiesel was always considered as a suitable alternative for diesel fuel in CI engines but higher NOx emissions still remains a challenge. Optimising the parameters like injection pressure and timing can yield significant reduction in NOx and smoke emissions. This experimental investigation was carried out with B20 blend (Palm Oil Methyl Ester 20% + neat diesel 80%) with varying pilot injection timing and pilot injection pressure in a common rail compression ignition diesel engine at part load condition. The results revealed that a reduction of 40% in NO emission was observed with the introduction of 10% pilot fuel and higher injection pressure at 32° bTDC compared with single injection mode at 23° bTDC. With the same strategy the smoke, HC and CO emission were found be lower at 34° bTDC by 26.2%, 19.2% and 21.5%. A slight increase in CO2 emission by 1.62% was noticed at 500 bar injection pressure at this injection timing compared to single injection mode.